Mitochondrial permeability regulates cardiac endothelial cell necroptosis and cardiac allograft rejection. Issue 3 (16th October 2018) - Gan, Ingrid; Jiang, Jifu; Lian, Dameng; Huang, Xuyan; Fuhrmann, Benjamin; Liu, Winnie; Haig, Aaron; Jevnikar, Anthony M.; Zhang, Zhu‐Xu
Abstract : Transplantation is invariably associated with programmed cell death including apoptosis and necrosis, resulting in delayed graft function and organ rejection. We have demonstrated the contribution of necroptosis to mouse microvascular endothelial cell (MVEC) death and transplant rejection. Organ injury results in the opening of mitochondrial permeability transition pores (mPTPs), which can trigger apoptotic molecules release that ultimately results in cell death. The effect of mPTPs in the necroptotic pathway remains controversial; importantly, their role in transplant rejection is not clear. In this study, tumor necrosis factor‐α triggered MVECs to undergo receptor‐interacting protein kinase family (RIPK1/3)‐dependent necroptosis. Interestingly, inhibition of mPTP opening could also inhibit necroptotic cell death. Cyclophilin‐D (Cyp‐D) is a key regulator of the mPTPs. Both inhibition and deficiency of Cyp‐D protected MVECs from necroptosis (n = 3, P < .00001). Additionally, inhibition of Cyp‐D attenuated RIPK3‐downstream mixed‐lineage kinase domain–like protein phosphorylation. In vivo, Cyp‐D–deficient cardiac grafts showed prolonged survival in allogeneic BALB/c mice posttransplant compared with wild‐type grafts (n = 7, P < .0001). Our study results suggest that the mPTPs may be important mechanistic mediators of necroptosis in cardiac grafts. There is therapeutic potential in targeting cell death via inhibition of the mPTP‐regulating molecule Cyp‐D to prevent cardiac graft rejection. Abstract : Mitochondria membrane permeability is an important mechanistic mediator of necroptosis in endothelial cells and an effective target for prevention of cardiac transplant rejection.